Evaluating the Quality of Service of Bus Performance in Johor Bahru - Bakar M.F.A.; Norhisham S.; Abudeyab N.H.Z.I.A.; Saad N.M.; Azlan N.N.I.M.; Shkuri N.S.M.; Mohamad A.M. (IOP Publishing Ltd, 2023)
The increase in living standard would also be a major factor for rapid urban development, which is caused by the increase in the daily traffic volume. Therefore, traffic congestion can occur daily, especially during peak hours in the morning and late afternoon to cover the huge number of people movement. Moreover, the quality of bus services should be assessed on operational aspects provided by urban operators. Therefore, this paper is to determine the quality of service (QOS) of bus performance in Johor Bahru, Johor. The study was conducted in April 2019. Service quality data were taken at Terminal JB Sentral, Johor Bahru. The Transit Capacity and Quality of Service Manual (TCRPM) was adopted as the specific guidelines and key indicators to determine and analyse the QOS of bus performance in the selected area. The study focused on four specific areas, such as service hour, passenger load factor, on-time performance and service frequency. The study concluded that the passenger load factor was classified as QOS of Class B since passengers could still choose their seats during the journey. On the other hand, on-time performance was classified as QOS of Class E, as most passengers made one round trip per weekday with a transfer experience of not-on-time vehicles every day. The overall QOS for bus services in Johor Bharu was classified as QOS of Class D, which was considered as moderate because several issues on QOS should be addressed and rectified by stakeholders. Some improvement on these three attributes should be made to increase the QOS. The study outcome should be used as an indicator for operators to measure their bus services. Since Johor Bahru is a major city in Malaysia, authorities and the government can use the outcome as inputs to measure the effectiveness of public transportation in urban areas. 2022 Institute of Physics Publishing. All rights reserved.